Year 2000 toolkit : a national plan for developing countries (World Bank WashingtonUS, 1998)
Focuses on aspects such as the implications of the year 2000 problem; strategies for managing the risk of the year 2000 problem; role of government; and the development and implementation of a national action plan.
Includes: 1 diskette